A learning workflow based on an integrated digital toolkit to support education in manufacturing system engineering. (April 2022) - Berardinucci, Francesco; Colombo, Giorgio; Lorusso, Marcello; Manzini, Massimo; Terkaj, Walter; Urgo, Marcello
Abstract: Digital modelling of manufacturing systems is experiencing a fast development, but it still shows significant limitations when considering integration and interoperability of enabling technologies. Indeed, there is still a lack of reference integrated workflows to perform the wide span of tasks, ranging from layout configuration and performance evaluations to 3D representations. Commercial software tools are either too complex or expensive to be approached by non-specialists, therefore it is hard to design effective learning activities in manufacturing system engineering. This paper proposes a structured learning workflow based on an open toolkit that takes advantage of a common ontology-based data model to smoothly integrate digital tools for manufacturing system modelling, performance evaluation, and virtual reality representation. After detailing methodologies and digital tools, the proposed workflow is applied to a pilot case in higher education. Highlights: Defining an integrated workflow to support higher-education learning activities in manufacturing system design and analysis. Requirements and examples of digital tools to support learning activities, contributions to the intended learning outcomes. A pilot implementation of the workflow for the design and analysis of an automated assembly line. A testing and validation of the proposed approach in the context of an Erasmus+ project. Links and references to a set of free tools and related documentation made available to teachers and students.